Gerhart Hauptmann's "Before Daybreak" A Translation and an Introduction - Bauland, Peter (UNC Studies in the Germanic Languages and Literatures, 1978)
"Before Daybreak", the first important drama of German naturalism, was also the first play of Gerhart Hauptmann, the most significant naturalist of the theater. This translation by Peter Bauland (originally published in 1978) is the first colloquially convincing English version that captures the several levels of diction in this seminal modern drama. It is preceded by a critical introduction by the translator which places the play in historical context and discusses its form and content.